Career interview with Professor Tamás Bánfi - Kürthy, Gábor (Public Finance Quarterly, 2024)
"How do you remember the beginning of your professional career?When I was in my fourth year of college, an important and fortunate series of events happened to me. I did not develop a personal relationship with any of the instruc-tors in the Finance Department during my first three years. I knew everyone and my relationship with them was polite and pleasant. But in the fourth year, we went on a plant visit to the Százhalombatta Thermal Power Plant. I don’t know whether it was because the students were not allowed to travel on the bus without an instructor or whether it was simply that the young István Hagelmayer, who had replaced Miklós Riesz as Head of the Department a year earlier, had found time to join us, but the point is that we travelled there and back with him."